Hubungan Dukungan Keluarga dan Dukungan Tenaga Kesehatan dengan Pemberian ASI Eksklusif di Wilayah Puskesmas Banjar Agung - Putri, Dwi Yunita Rahmalia; Koerniawati, Ratu Diah; Siregar, Mukhlidah Hanun (Poltekkes Kemenkes Yogyakarta, 2025)
Introduction: Exclusive breastfeeding is one of the efforts to overcome health and nutrition problems in children. Support from various parties, such as family and health workers, can affect the success of exclusive breastfeeding. Purpose: This research aimed to determine the relationship between family support and health worker support with exclusive breastfeeding. Method: This research used an observational design with a cross sectional approach. The research was conducted in the Banjar Agung Health Center working area, with a sample of 53 people, selected by purposive sampling method. Data were collected by direct interview using a questionnaire. Data were analyzed using the Chi-Square test. Result: The results showed that there were mothers with less family support (26,4%), less health worker support (50,9%), and did not provide exclusive breastfeeding (56,6%). The results of the analysis showed that there is an association between family support and exclusive breastfeeding (p = 0,025), but there is no association between health worker support and exclusive breastfeeding (p = 1,000). Conclusion: Intervention programs such as nutrition counselling and education for families, as well as training for health workers to strengthen their role in increasing exclusive breastfeeding are needed.